2010
DOI: 10.1063/1.3396084
|View full text |Cite
|
Sign up to set email alerts
|

Direct Wolf summation of a polarizable force field for silica

Abstract: We extend the Wolf direct, pairwise r −1 summation method with spherical truncation to dipolar interactions in silica. The Tangney-Scandolo interatomic force field for silica takes regard of polarizable oxygen atoms whose dipole moments are determined by iteration to a self-consistent solution. With Wolf summation, the computational effort scales linearly in the system size and can easily be distributed among many processors, thus making large-scale simulations of dipoles possible. The details of the implement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This method takes the summation of the Coulomb interactions entirely in the reciprocal space [78] causing the computational cost to scale as O(N 2 ) [77,[102][103][104] and, as it was noted previously, this is the main downside of the method.…”
Section: Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…This method takes the summation of the Coulomb interactions entirely in the reciprocal space [78] causing the computational cost to scale as O(N 2 ) [77,[102][103][104] and, as it was noted previously, this is the main downside of the method.…”
Section: Theorymentioning
confidence: 97%
“…Since this equation only requires evaluating of a pairwise sum truncated in an appropriate distance, the computational cost scales linearly with increasing system size (N), i.e., it is of order O(N) [42,62,70,82,85,93,104].…”
Section: Theorymentioning
confidence: 99%
“…This means that for small magnitudes of the wave vectors k, the charge structure factor is also small. In previous studies 16,23 it was shown that the reciprocal-space term is indeed negligible compared to the real-space part, provided that the splitting parameter κ is chosen small enough. As however a smaller κ results in a larger real-space cutoff r c , the latter has to be chosen three or four times the size of a typical shortrange cutoff radius in metals.…”
Section: B Wolf Summationmentioning
confidence: 99%
“…The term describing the electrostatic contribution to the total energy of the system consists of charge-charge, charge-dipole and dipole-dipole contributions. The Wolf summation was used for calculation of Coulomb interactions, (described in detail in [18,19]), with a cutoff of 13 Å . It was found that an Ewald parameter of j = 0.1 was sufficient.…”
Section: Force Fieldmentioning
confidence: 99%